PELATIHAN AKTIVITAS JASMANI ADAPTIF BERBASIS MERDEKA BERMAIN UNTUK ANAK BERKEBUTUHAN KHUSUS BAGI GURU TK - Diana - Diana (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2022)
This public submission aims to provide teachers with knowledge and skills in adaptive physical activity training for inclusive Early Childhood Education institutions by referring to the freedom-to-play principle. The initiative implemented physical activity training and adaptive physical activity designing in the framework of freedom to play based on the children’s needs. The community service was limitedly performed offline by imposing safety protocols. It involved 25 teachers who were members of the Kindergarten Education Teachers Association (IGTKI) in Semarang City. All necessary materials, in addition to direct practice of adaptive physical activities and adaptive physical activity designing based on the freedom to play, were given to children with special needs. The public submission activity was smoothly implemented, as it could contribute to providing knowledge for kindergarten teachers in designing and guiding adaptive physical activities for inclusive classes based on the freedom to play.